2001
DOI: 10.1097/00001756-200103260-00008
|View full text |Cite
|
Sign up to set email alerts
|

Contrast response characteristics of long-range lateral interactions in cat striate cortex

Abstract: Single-cell responses in visual cortex to a target falling within their receptive field can be modified by collinear flanking stimuli concurrently presented outside the receptive field. Here, we report the presence of four types of contrast-dependent lateral effects: (1) facilitation at low target contrasts and suppression at high contrasts, (2) facilitation that increases with contrast, (3) suppression that increases with contrast, and (4) suppression at low contrasts with facilitation at high contrasts. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 24 publications
4
93
2
Order By: Relevance
“…Sengpiel et al (1998) and Somers et al (1998) also reported similar e¡ects. Chen et al (2001) also reported another £anker e¡ect in which the £ankers increased cell response at all target contrasts and the amount of facilitation actually increased with target contrast. Notice that, in all these studies, £anker contrast was kept constant for each cell while the £anker e¡ect increased with target contrast.…”
Section: (A) Relationships Between Long-range Collinear Interactions mentioning
confidence: 87%
See 1 more Smart Citation
“…Sengpiel et al (1998) and Somers et al (1998) also reported similar e¡ects. Chen et al (2001) also reported another £anker e¡ect in which the £ankers increased cell response at all target contrasts and the amount of facilitation actually increased with target contrast. Notice that, in all these studies, £anker contrast was kept constant for each cell while the £anker e¡ect increased with target contrast.…”
Section: (A) Relationships Between Long-range Collinear Interactions mentioning
confidence: 87%
“…This`crossover' e¡ect should not be a surprise. Electrophysiological studies (Polat et al 1998;Chen et al 2001) have shown the crossover e¡ect that is most commonly seen (from 38% to more than 50% in di¡erent studies) in the collinear £anker e¡ect on single cell responses.…”
Section: Discussion (A) Sensitivity Modulation Factorsmentioning
confidence: 99%
“…CF input takes the form of high-contrast gabor patches that flank the central target in the upper and lower visual fields; see Figure 9 for example stimuli. Neurophysiological studies have demonstrated that, in this experimental setup, when flankers are presented concurrently with targets but placed outside the classical receptive field, the cell's response to the target is modulated [32,33]. Furthermore, due to the size of stimuli, orientation, contrast, and their wavelength, CF input can suppress detection of the centrally presented target gabor [32,33].…”
Section: Applications Of Id Measures To Psychophysical Datamentioning
confidence: 92%
“…Neurophysiological studies have demonstrated that, in this experimental setup, when flankers are presented concurrently with targets but placed outside the classical receptive field, the cell's response to the target is modulated [32,33]. Furthermore, due to the size of stimuli, orientation, contrast, and their wavelength, CF input can suppress detection of the centrally presented target gabor [32,33]. This paradigm is a suitable testbed for PID measures since it measures the influence of a modulatory input (CF), surrounding flanker stimuli, on performance, in this instance a contrast detection task on a centrally presented gabor (RF).…”
Section: Applications Of Id Measures To Psychophysical Datamentioning
confidence: 99%
“…Research on the properties of surround interactions has shown that the response of a V1 neuron can be increased or decreased by changing the relative contrast and0or orientation (Toth et al, 1996;Levitt & Lund, 1997;Polat et al, 1998;Chen et al, 2001;Mizobe et al, 2001) or direction of motion (Palmer & Nafziger, 2002) inside and outside the receptive field. However, there is skepticism whether increases in the activity of V1 neurons due to the presence of surround stimuli genuinely originate from beyond the classical receptive field (Walker et al, 2000).…”
Section: Introductionmentioning
confidence: 99%